R&D INTENSITY AND IPO UNDERPRICING: CASE STUDY ON PHARMACEUTICAL AND BIOTECH INDUSTRIES IN THE US - Tommy C. Efrata (Journal of Accounting and Investment, 2008)
Asymmetric information between the issuer to potential investors believed by some academics in finance as one of the main causes of the phenomenon of underpricing at the time of the initial public offering (IPO). On science and technology-based company main problem lies in how to conduct assessments on the future value of a product that is still in the development stage. The issue became more prominent on pharmaceutical companies and biotechnology, due to the characteristics of this industry is the high expense, complex process, and the lengthy process of research and development (R D) of a product. This study describes the characteristics above is associated with the phenomenon of underpricing when companies conduct IPO. The samples are 82 pharmaceutical companies and biotechnology conduct IPO in the United States stock market in 1998-2005. The results of this study revealed a negative correlation between the intensity of R D and IPO underpricing phenomenon in this industry. These studies have identified R D as the main source of information asymmetry that led to the phenomenon of underpricing for pharmaceutical companies and biotechnology.